Comparison of a team sport global positioning system and a video based motion tracking system in an elite competitive football environment - Li, F. X.; Dallaway, N.; Daley, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Professional football clubs are increasingly utilising GPS tracking systems to monitor players speed and distance run during training sessions in order to quantify the work load. Additionally, the video-based motion analysis system Prozone (PZ, Leeds, UK) tracks the players` movements in competitive matches. When both systems are used together they potentially provide a comprehensive account of the total distance and speeds covered by players in both training and competition. However, the relative accuracy of each system has not yet been evaluated. The aim of the study is to investigate the differences in the physical performance data from the PZ and GPS systems in an elite competitive football environment. Methods In a Barclay`s premier league reserve team fixture (UK), ten outfield players wore GPSport (Fyshwick, Australia) SPI Pro X 15Hz GPS units and were tracked via the PZ motion camera system. Data for overall distance, sprint distance (> 7m.s-1) and high speed distance (>5.5m.s-1) was compared between the 2 systems. Results In all cases GPS recorded lower distance and number of sprints than PZ. No significant difference was found for overall distance (GPS: 7717m ± 2389, PZ: 9341m ± 3288, p>.1). However significant differences were found between the high speed running (241m ± 140 compared to 645m ± 252,